Household decision making and the influence of spouses' income, education, and communist party membership: a field experiment in rural China - Fredrik Carlsson; Peter Martinsson; Ping Qin; Matthias Sutter (Institute for the Study of Labor (IZA), 2009)
We study household decision making in a high-stakes experiment with a random sample of households in rural China. Spouses have to choose between risky lotteries, first separately and then jointly. We find that spouses' individual risk preferences are more similar the richer the household and the higher the wife's relative income contribution. A couple's joint decision is typically determined by the husband, but women who contribute relatively more to the household income, women in high-income households, women with more education than their husbands, and women with communist party membership have a stronger influence on the joint decision.
urn:nbn:de:101:1-20090513377
Keywords: C91; C92; C93; D10; 330; Household decision making; risk; field experiment; China; Haushaltsökonomik; Feldforschung; Ländlicher Raum; China